2023
DOI: 10.3389/fimmu.2023.1170012
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the pro-inflammatory cytokine signature in severe COVID-19

Abstract: Clinical outcomes from infection with SARS-CoV-2, the cause of the COVID-19 pandemic, are remarkably variable ranging from asymptomatic infection to severe pneumonia and death. One of the key drivers of this variability is differing trajectories in the immune response to SARS-CoV-2 infection. Many studies have noted markedly elevated cytokine levels in severe COVID-19, although results vary by cohort, cytokine studied and sensitivity of assay used. We assessed the immune response in acute COVID-19 by measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 61 publications
0
4
1
Order By: Relevance
“…Some cytokines, such as TNF-α and IL-10, have been associated with COVID-19 severity and mortality in other studies [ 16 , 37 , 38 ], but was not found to be significantly different between survivors and non-survivors after Bonferroni correction in our study. Infliximab, a TNF-α inhibitor, was shown to lower 28-day mortality in a selected group of patients with COVID-19, suggesting a role of TNF-α in the pathogenesis of more severe COVID-19 [ 39 ].…”
Section: Discussioncontrasting
confidence: 77%
“…Some cytokines, such as TNF-α and IL-10, have been associated with COVID-19 severity and mortality in other studies [ 16 , 37 , 38 ], but was not found to be significantly different between survivors and non-survivors after Bonferroni correction in our study. Infliximab, a TNF-α inhibitor, was shown to lower 28-day mortality in a selected group of patients with COVID-19, suggesting a role of TNF-α in the pathogenesis of more severe COVID-19 [ 39 ].…”
Section: Discussioncontrasting
confidence: 77%
“…First hypothesis is that the virus or vaccine may trigger an autoimmune response that targets the brain, leading to inflammation and neuronal injury [13]. COVID-19 infection and vaccination-associated GCSE have showed the elevated levels of pro-inflammatory cytokines in their cerebrospinal fluid [14]. Second hypothesis is that the virus or vaccine may induce an allergic reaction that results in cerebral edema and seizures [15].…”
Section: Discussionmentioning
confidence: 99%
“…In 118 hospitalized COVID-19 patients (78% considered severe), 0.11 pg./mL median IL-1β was measured in plasma. In 44 healthy controls 0.10 pg./mL was observed with no difference in levels determined between COVID-19 patients and controls ( Hawerkamp et al, 2023 ). Serum IL-1β was measured in 46 COVID-19 patients in intensive care (median 0.35 pg./mL), in 30 COVID-19 patients not in intensive care (median 0.32 pg./mL), and in 24 healthy volunteers (median IL-1β 0.11 pg./mL).…”
Section: Introductionmentioning
confidence: 88%
“…This imprecision, combined with the advent of multiplex assay platforms that can simultaneously measure up to 100 molecules in blood ( Kupcova Skalnikova et al, 2020 ) has resulted in conflicting reports enumerating molecules relevant for linking sepsis to inflammation. A sampling of COVID-19 reports list blood levels for 20 ( Hawerkamp et al, 2023 ), 27 ( Huang et al, 2020 ), 35 ( Mudd et al, 2020 ), 48 ( Tjan et al, 2021 ), or 53 ( Herr et al, 2021 ) molecules. These quantifications include molecules thought to be pro-inflammatory like IL-1 and TNF, anti-inflammatory cytokines such as IL-6 and IL-10, interferons, chemokines, soluble cell receptors, complement components, ferritin, tumor markers, the acute-phase protein CRP, procalcitonin, and chitinase 3-like 1 (YKL-40).…”
Section: Introductionmentioning
confidence: 99%